Typhoid Salmonella Strains in Pakistan Posing a Potential Risk to Drug-Resistant (Medical Forum Monthly, 2024)
Objective: The objective of this cross sectional research study will be to determine the proportion of total and drug resistant Salmonella Typhi strains in 100 patients admitted in hospitals with typhoid fever in Pakistan.Study Design: A Cross sectional study .Place and Duration of Study: This study was conducted at the Department of Pediatrics Medicine, University of Medical and Health Sciences for Women Nawabshah Sindh. From 1st Jan 2022 to 30th September 2022.Methods: A descriptive cross-sectional design was adopted for the study whereby one hundred patients diagnosed with typhoid fever were included in the study. Blood specimen were obtained and inoculated into culture media to isolate Salmonella Typhi. As typing to determine drug resistance, antibiotic susceptibility testing was done. Descriptive statistics was conducted on SPSS version 24.0 and the level of significance used in analysis was p < 0.05.Results: Of the 100 patients, 60 % of the patients were positive for drug resistant S. Typhi. The overall mean age of the patients enrolled in the study was thirty one point three years (SD ± 6.5). MDR was observed in this study to be 45%, with recipe for ciprofloxacin at p = 0.03. Total duration of stay also differed significantly in drug resistant bacteria patients who took longer time to recover than patients with non-resistant bacteria (mean= 14.5 days, p < 0.05).Conclusion: The study shows a worrisome trend of multiresistant S. Typhi in Pakistan, based on its results. This demands for more emphasis on the public health measures to prevent or reduce the use of antibiotics as well as enhance sanitization in addition to emergence of new therapeutic approaches against the strains.